FUNCTIONALITY AND QUALITY OF LIFE IN ELDERLY PEOPLE SUBMITTED TO TOTAL KNEE ARTHROPLASTY - Leonel Preto; Claúdia Pinto; André Novo; Eugénia Mendes; Ilda Barreira; Fidel Lopez-Espuela (Associação Portuguesa dos Enfermeiros de Reabilitação, 2019)
Objective: To evaluate perception of knee functionality and health-related quality of life (HRQL) in elderly patients submitted to total knee arthroplasty (TKA). Methods: 40 patients were studied at two moments of evaluation: in the preoperative period and eight weeks after surgery. HRQL was assessed using the MOS-SF-36 v2 (Medical Outcomes Study 36-Item Short-Form Health Survey) and KOOS (Knee Injury and Osteoarthritis Outcome Score). Results: Sample (71.6 ± 8.1 years), mostly female (62.5%). The SF-36 v2 MOS results show an improvement in all dimensions of physical health in the second evaluation (p <0.05). In the field of mental health there has also been improvement in all dimensions, except vitality. The functionality of the knee improved in the subscales: symptoms (p = 0.015), pain (p <0.001) and quality of life (p <0.001). Conclusion: Patients evaluated eight weeks after TKA showed improvements in self-perceived health, quality of life, physical performance and pain.